Uma impressão a cada viagem: percepção da natureza do pampa na visão de viajantes europeus 1818-1858 - Minuzzi, João Davi Oliveira (2017)
This text presents the results of my master's research about the analysis of five travel reports. The reports chosen are from travelers Alexander Baguet, Arsène Isabelle, Auguste de Saint-Hilaire, Nicolau Dreys and Robert Avé-Lallemant. The objective of this work is to understand how these travelers perceived the environment of Pampa, an unknown territory to them. These reports may give us a complex understanding of the relationships established between humans and the natural world, especially with regard to the temporal space of research that is the Pampa in the first half of the nineteenth century. This region still lacks studies in the area and it is interesting because it is a biome divided by borders of States that were formed and consolidated in that period, trying to get more influence in this vast region. In this perspective, I use environmental history as a theoretical reference to perform the analysis of the sources.